Mindfulness dan tawakal untuk mengurangi depresi akibat pemutusan hubungan kerja pada karyawan di era pandemi covid-19 - Iva Nining Riyanty; Annisaa Miranty Nurendra (Fakultas Psikologi, 2021)
Covid 19 has had quite a complex impact on various areas such as the health, education and industry sectors. Termination of employment by the company has an impact on the psychological health of workers such as depression. Mindfulness and tawakal play a role in minimizing depression due to the termination of employment as well as being a barrier for terminated employees to stay psychologically healthy by submitting their difficult situation to Allah. The purpose of this literature study is to determine the positive impact of mindfulness and tawakal in reducing depression due to layoffs. This literature study is an attempt to develop psychological studies including Islamic psychology in the Covid-19 pandemic era. The reviewed literature includes scientific journals and popular articles on trusted sites. The results of the review of several references state that mindfulness has a positive impact on reducing depression due to layoffs. The nature of tawakal has a positive impact on individuals to remain surrender to Allah and keep trying their best, and this behavior can also reduce depression due to layoffs (layoffs). The results are expected to be applied as a preventive measure to minimize depression due to layoffs.